The Degradation of Distorted Performance Measures - Randolph Sloof; Mirjam van Praag (Tinbergen Institute, 2008)
Baker (2002) has demonstrated theoretically that the quality of performance measures used in compensation contracts hinges on two characteristics: noise and distortion. These criteria, though, will only be useful in practice as long as the noise and distortion of a performance measure can be measured. Courty and Marschke (2007) have recently developed an elegant empirical test to detect distortion, based on the degradation of a performance measure subsequent to increasing its weight in the remuneration contract. We apply their test to assess the distortion of the often used class of performance measures that are based on `Residual Income' (RI), such as `Economic Value Added' (EVA). Residual income is widely used to measure and reward the performance of management boards. We use a difference-in-difference approach to account for (a) changes in economic circumstances in the period studied and (b) the self-selection of firms into the treatment and the control groups. Our results show that RI has degraded and is, therefore, a distortionary performance measure that can be gamed.
Keywords: D21; G35; J33; L21; M12; M41; M52; 330; Residual income; EVA; degradation; distortion; performance measurement; management compensation; incentive compensation; Leistungsbeurteilung; Führungskräfte; Performance-Messung; Leistungsentgelt; Anreizvertrag; USA